Location of Pulp Chamber in Lower First Permanent Molars: In-Vitro Study - Dall, Abdul Qadir Khan; ., Sarwanand; Batool, Sarwat; Arora, Suraj; Qureshi, Saifullah (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To determine whether the pulp chamber floor of mandibular first permanent molars is always centrally located (law of centrality) at the level of cemento enamel junction (CEJ) or off-centered (mesiobuccally). Methodology: This cross-sectional analytical study was conducted at Dental OPD Liaquat University of Medical & Health Sciences, Jamshoro / Hyderabad from June to December 2017 with probability consecutive sampling technique. Total 384 extracted teeth were decoronated at cemento-enamel junction level and photographed. Paint milimeter grid was superimposed on photograph and position of pulp chamber was measured centered or off-centered. Inclusion Criteria was set as ages of 20 to 60 years of either gender, included extracted mandibular first permanent molar teeth of both genders with intact crown and root morphology without any restoration and dentin caries. Endodontically treated teeth, heavily restored teeth, and teeth with deep non-carious cervical lesions were excluded. The collected data was analyzed on SPSS version 16, with p-value of less than 0.05. Results: Total 55.7% (n=214) specimens were observed to have mesiobuccal off-center location of pulp chamber and 44.7% (170) had centrally located pulp chamber (P-value 0.007). In age-group1 (20-40 years), 140 specimens observed with centrally located pulp chamber and only 20 specimens had off-center location of pulp chamber. In age-group2 (41-60 years), 30 specimens had central location while 194 observed to have off-centered (mesiobuccally) position of pulp chamber (p-value of 0.001). Conclusion: Location of the pulp chamber of mandibular first molar is mesiobuccally off-centered in majority of specimens